The Effectiveness of Group Counseling with Cognitive Restructuring Technique to Improve Students’ Emotion Regulation and Self-Esteem - Riyadah, Riyadah; Eddy Wibowo, Mungin; Sunawan, Sunawan (Universitas Negeri Semarang, 2021)
Students’ ability to manage emotion is crucial to achieve academic success at school. Thus, the present research attempted to improve emotion regulation and self-esteem through the group counseling with cognitive restructuring technique. 28 Junior High School students chosen using purposive sampling technique were involved in a series of experiment in pretest and posttest control group design. Emotion regulation and self-esteem scales were employed to collect the data. After the analysis of repeated mixed manova test, it was noticed that the cognitive restructuring technique was effective to improve emotion regulation and self-esteem. It clarifies the effectiveness of CBT to improve emotion regulation and self-esteem.